OP67 Considerations Of Treatment Novelty In Health Technology Assessment. (23rd December 2022) - Synnott, Patricia; Enright, Daniel; Voehler, Dominic; Kowal, Stacey; Ollendorf, Daniel
Abstract : Introduction: A recent proliferation of value frameworks, as well as the emergence of innovative approaches to treating disease (e.g., cell/gene therapies) have been accompanied by an increased focus on nontraditional elements of value. We sought to understand whether and how health technology assessment (HTA) agencies consider novel aspects of treatment in value assessments. Methods: We defined treatment novelty as follows: (i) a new mechanism of action or administration; (ii) addresses an unmet need; or (iii) confers a distinct benefit that transforms clinical practice or that is difficult to quantify. We reviewed technical guidance and peer-reviewed literature to investigate how organizations in eight countries (Australia, Canada, England, France, Norway, the Netherlands, Sweden, and the United States) consider aspects of this definition. Results: All (n = 8) organizations give special consideration to interventions that address an unmet need, particularly in cancer, rare diseases, and other severe conditions. Nearly all (n = 5) organizations consider whether an intervention produces benefits that may not be adequately quantified. Organizations in England, Norway, and France sometimes recommend drugs with less favorable cost-effectiveness estimates than traditionally considered if the drug addresses rare or severe conditions, or if its quality-of-life benefit is thought to be inadequately quantified. The Institute for Clinical and Economic Review in the United States models cost-effectiveness in rare diseases using both a modified societal and health care system perspective. Importantly, the benefits of novel treatments are frequently considered uncertain, particularly treatments with a new mechanism of action. When uncertainty is high, organizations in Canada, England, France, the Netherlands, and Sweden sometimes issue conditional recommendations until additional evidence is submitted. England and Australia have used risk sharing agreements for drugs determined to be novel but uncertain. Conclusions: The most widely considered aspects of treatment novelty in HTA are unmet needs and potential benefits that are not easily measured. The willingness to pay for novel treatments is often greater, despite inherent uncertainties about benefit and cost-effectiveness.